Resveratrol in the treatment of asthma based on an animal model - Leis, Kamil; Gałązka, Przemysław; Kazik, Jakub; Jamrożek, Tomasz; Bereźnicka, Weronika; Czajkowski, Rafał (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2022)
Resveratrol is a natural polyphenol found, for example, in red wine, grapes or nuts. One of the resveratrol’s health properties is a cardioprotective activity – it is believed that resveratrol is responsible for the French paradox and anticancer activity. Moreover, the effectiveness of resveratrol in the treatment of asthma is confirmed by multiple research. Resveratrol displays a multiway impact on the reduction of the symptoms of the disease which contributes to the alleviation of inflammation i.a. by: inhibition of cellular infiltration, suppression of oxidative stress, reduction in the volume of mucus, relaxation of smooth muscle, stalling of the fibrosis affecting the respiratory tract or counteracting bronchial hyperresponsiveness. Resveratrol reduces the concentration of eosinophils, pro-inflammatory interleukins and interferes with many signal transduction pathways. In case of concomitance of obesity, resveratrol alleviates the course of asthma. The review juxtaposes the mechanisms of resveratrol activity and presents the results of the published research conducted on rodents.